Peran Shah Waliyullah al-Dihlawi sebagai Katalisator Perkembangan Tafsir di Asia Selatan - Muhammad Rijalul Fikri; Nur Komariah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2025)
The history of Qur’anic exegesis in South Asia is often framed within a binary periodization of classical-traditional versus modern-reformist eras, which tends to overlook transitional figures. This study highlights Shah Wali Allah al-Dihlawi (1703–1762 CE) as a pivotal catalyst in the transformation of modern exegesis in the region. Employing qualitative methods and an intellectual history approach, it examines two of his major works Al-Fawz al-Kabir fi Usul al-Tafsir and Hujjat Allah al-Balighah alongside relevant secondary literature. The findings indicate two key epistemological shifts: first, the systematization of exegetical methodology through the classification of Qur’anic verses into five principal themes, redirecting the focus from mere transmission of knowledge or naql to a structured construction of exegetical science; second, the pursuit of rational wisdom and universal objectives, or maqasid underlying legal rulings, moving beyond legal-formalism toward a more philosophical-hermeneutical understanding. This legacy evolved into two currents of modern exegesis: the rationalist-accommodative strand associated with Sayyid Ahmad Khan and the activist-ideological strand associated with Sayyid Abul A‘la Maududi. The study concludes that Shah Wali Allah is a key transitional figure bridging classical traditions with modern challenges.